KONDISI VEGETASI HABITAT TARSIUS (Tarsius dentatus) DI RESORT LINDU TAMAN NASIONAL LORE LINDU PROVINSI SULAWESI TENGAH - Tikuliling, Febriyanti Sali; Labiro, Elhayat; Sustri, Sustri (Jurnal Warta Rimba, 2015)
Abstract Lore Lindu National Park is one of conservation areas located in Central Sulawesi, which has a unique both in terms of ecosystems and the flora and fauna that exist in it. One of the unique fauna is tarsier (Tarsius dentatus). Tarsius dentatus is categorized as vulnurable by International Union for Conservation of Nature (IUCN) Red List and on appendix II of the Convention on International Trade in Endangered Species (CITES). This study was conducted in Resort Lindu, Lore Lindu National Park from March to June 2014. This study aims to identify the vegetation condition of the tarsier habitat in Lore Lindu National Park. Vegetation analysis in this study used a single plot placed intentionally (purposive sampling). Sample plot observation was made of a square with a size of 0.25 ha or 50 m x 50 m. Result of study found 95 species of vegetation from 55 families, either trees, poles, saplings, or seedlings and understorey plants at two habitats of tarsier. The dominant plant species for seedlings namely: Calamus sp. (26.60%) and Neprolepis sp. (24.21%). At the sapling stage is Piper aduncum L. (44.36%;63.60%). At the pole stage is Piper aduncum L. (44.68%;47.05%). Whereas, at the tree stage are Ficus sp. 3 (30.78%) and Casuarina equisetifolia L. (28.64%). Species diversity index (H') in the two study sites might be classified as moderate to high, ie between (2.97 to 3.16). Keyword: Tarsier, Tarsius dentatus, Vegetation, Species diversity, Lore Lindu National Park.